Morphological Assessments of Root Apex of Permanent Mandibular First and Second Premolars in a Turkish Population - Babayeva, Fidan; Orhan, Ekim Onur; Irmak, Ozgur (Image Analysis and Stereology, 2021)
There is no apical morphological data being available for mandibular first or second premolars in the Turkish population. The aims of the study were (I) to assess apical morphological data of mandibular first and second premolars in a Turkish population at a young-adult age range (II) to analyze potential correlations between the size and position of the apical foramina (AF). Extracted sound teeth were collected from an adult volunteer population as willing to donate. Morphological data were obtained from specimens using a stereomicroscope. The number, size, shape, and position of AF and frequency of accessory foramina were quantified. Mann-Whitney U and Spearman's rank correlation tests were performed (α=0.05). A total of 237 teeth were investigated. The majority of the specimens had one major AF. The frequency of major AF was between 1–3 for both groups. The median AF size in mandibular first and second premolars were 55,180 µm2 and 67,483 µm2, respectively. The majority of foramina shape was irregular for the mandibular first premolars whereas, was oval for the second premolars. The median location of AF with respect to the anatomic apex was 664 µm in mandibular first premolars and 677 µm in mandibular second premolars. The size and location of AF mostly overlap between the mandibular first and second premolars. The shape of the AF might be the only relevant variation concerning the apical morphology between the mandibular first and second premolars in young adults. The interaction between the size and location of AF in mandibular premolars of young adults seems not significant